2013
DOI: 10.1016/j.chroma.2012.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of salting-out assisted liquid/liquid extraction for multi-mycotoxin biomarkers analysis in pig urine with high performance liquid chromatography/tandem mass spectrometry

Abstract: (2013). Development and application of salting-out assisted liquid/liquid extraction for multi-mycotoxin biomarkers analysis in pig urine with high performance liquid chromatography/tandem mass spectrometry. Journal of Chromatography A, 1292Chromatography A, , 111-120. 10.1016Chromatography A, /j.chroma.2012 AbstractDirect determination of urinary mycotoxins is a better approach to assess individual's exposure than the indirect estimation from average dietary intakes. In this study, a new analytical method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 31 publications
0
68
1
1
Order By: Relevance
“…2 Effects of different a loading solvents and b flow rates on IAC efficiency 0.30-25, 0.30-25, and 1.2-40 μg kg −1 , respectively. These linear ranges were larger than those of previous studies on multiple mycotoxins in body fluids (urine and plasma) [22].…”
Section: Matrix-matched Calibration Curves and Linear Rangecontrasting
confidence: 61%
“…2 Effects of different a loading solvents and b flow rates on IAC efficiency 0.30-25, 0.30-25, and 1.2-40 μg kg −1 , respectively. These linear ranges were larger than those of previous studies on multiple mycotoxins in body fluids (urine and plasma) [22].…”
Section: Matrix-matched Calibration Curves and Linear Rangecontrasting
confidence: 61%
“…Thanks to the high sensitivity of the recently developed analytical instruments, different liquid chromatography tandem mass spectrometry methods (LC-MS/MS) for the detection and quantification of biomarkers in urine were developed in order to assess mycotoxin exposure (Ediage et al, 2012;Gambacorta et al, 2013;Rodriguez-Carrasco et al, 2014b;Solfrizzo et al, 2011Solfrizzo et al, , 2013Song et al, 2013;Warth et al, 2011Warth et al, , 2013b. Only recently, results of epidemiological studies were increasingly reported whereby the exposure to mycotoxins in different populations was assessed through biomarkers.…”
mentioning
confidence: 98%
“…To facilitate the phase separation and to reduce the miscibility of the analytes in the aqueous phase, this protocol adopted the approach of salting-out-assisted liquid-liquid extraction (SALLE), adding salt (NaCl) prior to the liquidliquid extraction to favour the transfer of the analytes into the organic solvent [26][27][28].…”
Section: Sample Preparationmentioning
confidence: 99%